Synthesis of 2-Amino-4-(3-amino-5-hydroxy-4H-pyrazol-4-ylidene)-4H-chromene-3-carbonitriles - Mane, Mansing M.; Pore, Dattaprasad M. (Synlett, 2016)
A simple and efficient protocol was developed for the synthesis of 2-amino-4-(3-amino-5-hydroxy-4H-pyrazol-4-ylidene)-4H-chromene-3-carbonitriles by the potassium phosphate-catalyzed reaction of salicylaldehydes, malononitrile, and 2-cyanoacetohydrazide in ethanol. The method offers advantages such as a simple workup procedure and good yields. When the method was extended to two equivalents of 2-cyanoacetohydrazide instead of malononitrile, the unexpected formation of a salicylaldehyde azine was observed, leading to a novel route for the synthesis of salicylaldehyde azines.
Keywords: pyrazoles; chromenes; cyclization; multicomponent reactions; azines